Widening East-West inequality in life expectancy in Europe during the COVID-19 pandemic: An international comparative study - Vladimir M. Shkolnikov; Sergey Timonin; Dmitri Jdanov; Naomi Medina-Jaudes; Nazrul Islam; David A. Leon (PLoS ONE, 2026)
For decades, life expectancy in Eastern Europe has lagged behind that in Western Europe, although the gap has narrowed since the mid-2000s. We examined the impact of the COVID-19 pandemic on these long-term trends by estimating and decomposing East-West differences in excess mortality and life expectancy losses. Regression models were used to explore the contribution of multiple factors to the observed differences. While excess mortality was initially low in Eastern Europe, partly due to lower air connectivity, by October 2020 and throughout 2021, the region experienced significantly higher life expectancy losses than Western Europe. These differences could not be attributed to greater frailty in the Eastern European populations. Rather, lower vaccination coverage and less trust in government in Eastern Europe explained about half of the gap in 2021. After the peak of the pandemic, the East-West gap in life expectancy began to narrow again. Our findings highlight that the factors behind the East-West differences in the timing and severity of pandemic-related mortality may have their ultimate origins in differences between societies that were established during the Cold War. Strengthening public health infrastructure and social trust should be considered to mitigate the unequal impact of future crises.